Hippocampus-centred grey matter covariance networks predict the development and reversion of mild cognitive impairment - Mingxi Dang; Caishui Yang; Kewei Chen; Peng Lu; He Li; Zhanjun Zhang; for the Beijing Aging Brain Rejuvenation Initiative, for the Alzheimer’s Disease Neuroimaging Initiative (Alzheimer’s Research & Therapy, 2023)
Abstract Background Mild cognitive impairment (MCI) has been thought of as the transitional stage between normal ageing and Alzheimer’s disease, involving substantial changes in brain grey matter structures. As most previous studies have focused on single regions (e.g. the hippocampus) and their changes during MCI development and reversion, the relationship between grey matter covariance among distributed brain regions and clinical development and reversion of MCI remains unclear. Methods With samples from two independent studies (155 from the Beijing Aging Brain Rejuvenation Initiative and 286 from the Alzheimer’s Disease Neuroimaging Initiative), grey matter covariance of default, frontoparietal, and hippocampal networks were identified by seed-based partial least square analyses, and random forest models were applied to predict the progression from normal cognition to MCI (N-t-M) and the reversion from MCI to normal cognition (M-t-N). Results With varying degrees, the grey matter covariance in the three networks could predict N-t-M progression (AUC = 0.692–0.792) and M-t-N reversion (AUC = 0.701–0.809). Further analyses indicated that the hippocampus has emerged as an important region in reversion prediction within all three brain networks, and even though the hippocampus itself could predict the clinical reversion of M-t-N, the grey matter covariance showed higher prediction accuracy for early progression of N-t-M. Conclusions Our findings are the first to report grey matter covariance changes in MCI development and reversion and highlight the necessity of including grey matter covariance changes along with hippocampal degeneration in the early detection of MCI and Alzheimer’s disease.